Preparation of Calcium Tablets from Nano Calcium Carbonate Synthesized from Chicken Egg Shells - Thu Huong, Pham; Hung Thinh, Pham; Thi Anh Thu, Huynh; Thi Dieu Hoa, Nguyen; Thi Thu Ha, Nguyen; Thi Minh Hong, Truong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Abstract: Calcium is an essential mineral for the body, participating in the process of hemostasis, nerve conduction and muscle activity. Meanwhile, chicken eggshells contain a large amount of calcium carbonate, which is often discarded and poses a risk of environmental pollution. The research was conducted to develop the formula and process of preparing calcium tablets from nano calcium carbonate synthesized from chicken eggshells, and at the same time evaluate the properties of the raw materials in the finished tablets. Tablets were prepared by wet granulation method, examining the effects of various fillers (lactose monohydrate, corn starch, avicel pH 101), disintegrants (crospovidone, sodium croscarmellose, sodium starch glycolate), and lubricants (magnesium stearate, talc) on 10 experimental formulations. The optimal formulation for 150 mg tablets, including 75 mg nano calcium carbonate (50%) corresponding to about 30 mg elemental calcium along with 42% corn starch, 4% crospovidone, 3% polyvinylpyrrolidone and 1% magnesium stearate. The test results showed that the tablets met the requirements of the Vietnamese Pharmacopoeia V in terms of mass uniformity, disintegration, solubility and abrasion resistance. The properties of nano calcium carbonate in finished tablets were evaluated by scanning electron microscopy, X-ray diffraction, infrared spectroscopy and differential thermal analysis. The results showed that nano calcium carbonate retained its morphological properties and crystal structure, had no adverse interactions with excipients and was not affected by the preparation process. The study contributes to the utilization of eggshell waste, and at the same time provides a calcium supplement of natural origin and low cost. Keywords: Nano calcium carbonate, calcium tablets preparation, wet granulation method, excipients.